EMPOWERMENT OF THE BISIMO ETAIKENA FARMER GROUP IN PROCESSING BANANA PEEL WASTE INTO NATA DE MUSA - Tuhuteru, Sumiyati; Yohanes Rumbiak, Rein Edward; Inrianti, Inrianti; Himan, Rusina; Lengka, Mariana (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Nata is a food product from a fermentation process like banana peels. The requirement for making Nata products. Generally, the basic ingredients must have a fairly high glucose (carbohydrate) content. Banana peel is a waste material (banana fruit waste) which is quite a lot. Banana peel waste contains high levels of nutrients, especially vitamins, and minerals, so that it can be used as food raw material. Banana peel waste is good enough to be used as a substrate for making nata de Musa; judging from the nutritional content, it has a fairly high carbohydrate content. This empowerment activity is carried out through the Beginner's Community Service Program (PMP) for Fiscal Year 2023, funded by the Directorate of Research, Technology, and Community Services (DRTPM). This activity took place in Wamena City, Jayawijaya Regency, Papua Highlands Province, from July to August 2023, with the participation of 20 farmers. This community service initiative uses the Community Based Research (CBR) methodology for training and mentoring, specifically the Forum Group Discussion (FGD) technique. The results of this community service activity show a great opportunity to develop and continue as a community micro and medium business with processed banana skin waste products